Posterior Vertebral Column Resection (pVCR) for Severe Thoracolumbar Kyphosis in Patients With Achondroplasia - Wang, Hai; Wang, Shengru; Wu, Nan; Wang, Shujie; Qiu, Guixing; Zhang, Jianguo (Global spine journal, 2022)
Study Design: Retrospective cohort study. Objective: We aimed to evaluate the safety and validity of posterior vertebral column resection (pVCR) for severe thoracolumbar kyphosis (TLK) in the achondroplasia (ACH) patients. Methods: Seven ACH patients (male: female = 6:1) who underwent pVCR procedures due to severe TLK from December 2008 to December 2017 in the authors’ hospital were included in this retrospective study. Their mean follow-up duration was 67 ± 35 months. Their clinical characteristics, radiologic characteristics, surgical characteristics and surgical complications were reviewed. Results: A total of 8 vertebrae were removed with an average of 5 ± 2 levels of decompression and 9 ± 2 segments instrumented. The mean correction rates of TLKs and the main curves were 73 ± 15% and 87 ± 6%, respectively. Five patients (71%) had preoperative neurological symptoms with a mean Japanese Orthopedic Association (JOA) score of 8 ± 3 points. Their neurological functions were all improved, with a recovery rate of 78 ± 32% for the JOA score at the last follow-up. Four patients (57%) suffered from surgical complications, including rod breakages (43%), neurological complications (28%), dural tears (14%), cerebrospinal fluid leaks (14%) and proximal junction kyphosis (14%). Conclusions: pVCR can offer a good correction for TLK and improve neurological function with extensive laminectomies in ACH patients. But the morbidity of surgical complications is relatively high. Therefore, it is a reserved surgical option for severe TLK in ACH patients by experienced spinal surgeons, especially with apical markedly hypoplastic vertebrae.